2013
DOI: 10.1371/journal.pone.0074613
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures in Excess of Critical Thresholds Threaten Nestling Growth and Survival in A Rapidly-Warming Arid Savanna: A Study of Common Fiscals

Abstract: Frequency, duration, and intensity of hot-weather events are all predicted to increase with climate warming. Despite this, mechanisms by which temperature increases affect individual fitness and drive population-level changes are poorly understood. We investigated the link between daily maximum air temperature (tmax) and breeding success of Kalahari common fiscals (Lanius collaris) in terms of the daily effect on nestling body-mass gain, and the cumulative effect on size and age of fledglings. High tmax reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
201
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(214 citation statements)
references
References 33 publications
9
201
4
Order By: Relevance
“…For tropical species at lower air temperatures and higher humidity the thermal endpoints may be significantly lower (Weathers, 1997). Studies of wild birds in arid habitats have identified important threshold T a values in the 30-40°C range for variables related to body condition (du Plessis et al, 2012) and provisioning rates during breeding (Cunningham et al, 2013), suggesting that in many cases, detailed models of specific determinants of survival and/or reproduction will be necessary to predict the effects of climate change. However, catastrophic mortality events during extreme heat waves in the arid zones of Australia and elsewhere (reviewed by McKechnie et al, 2012;McKechnie and Wolf, 2010), combined with predicted increases in the frequency and intensity of heat waves (IPCC, 2011), underscore the relevance of models of avian survival over time scales of hours during acute heat exposure, and the need for comparative data on the upper limits of avian heat tolerance.…”
Section: Scaling Of Heat Tolerancementioning
confidence: 99%
“…For tropical species at lower air temperatures and higher humidity the thermal endpoints may be significantly lower (Weathers, 1997). Studies of wild birds in arid habitats have identified important threshold T a values in the 30-40°C range for variables related to body condition (du Plessis et al, 2012) and provisioning rates during breeding (Cunningham et al, 2013), suggesting that in many cases, detailed models of specific determinants of survival and/or reproduction will be necessary to predict the effects of climate change. However, catastrophic mortality events during extreme heat waves in the arid zones of Australia and elsewhere (reviewed by McKechnie et al, 2012;McKechnie and Wolf, 2010), combined with predicted increases in the frequency and intensity of heat waves (IPCC, 2011), underscore the relevance of models of avian survival over time scales of hours during acute heat exposure, and the need for comparative data on the upper limits of avian heat tolerance.…”
Section: Scaling Of Heat Tolerancementioning
confidence: 99%
“…They comprise the extreme tails of the temperature distribution at the study site, representing the most extreme conditions experienced by these species. Although various studies have identified air temperatures ≥35°C as thresholds for temperaturerelated mass loss, these are for arid and semi-arid species inhabiting hot environments [10][11][12][13]. Species in cooler, mesic climates may have inflections in evaporative water loss at lower air temperatures, in the region of 30°C [40].…”
Section: Data (I) Bird Datamentioning
confidence: 99%
“…The need to dissipate heat can lead to trade-offs with foraging, resulting in reduced foraging efficiency or effort, leading to reductions in body condition [10,11]. In addition, nonpanting forms of heat dissipation (e.g.…”
Section: Spring and Summermentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on how historical warming may already be contributing to the reduced fitness of certain bird species (e.g. Cunningham et al 2013;Du Plessis et al 2012). However, the impact of historical and projected climate change on vegetation change in the southern Kalahari has received less attention, probably because of the difficulty of separating the influence of multiple interacting drivers of change that operate at different temporal and spatial scales.…”
Section: Introductionmentioning
confidence: 99%